Features of geochemical processes in the catchment area of the river Kalaus in the Stavropol territory - Anastasia Sergeevnna Bluzhina; Inna Vladimirovna Begday (Наука. Инновации. Технологии)
The article, based on the calculated coefficients of geochemical analyzes the distribution of heavy metals in system «plant - soil - natural water - bottom sediments» agro-landscapes Kalaus river in the Stavropol Territory. On the basis of geochemical biogeochemical factors made up the formula for Dobrovolsky V.G. for landscape-geochemical catena section flowing river Kalaus. In the study of migration features of chemical elements in the lowland areas of the river used factor analysis. To conirm the connection between the metal content in sediments relative to the soil wheat fields we compiled correlation matrices for the studied landscape geochemical catenas. As a result of the analysis of the matrix revealed a characteristic pattern of behavior of elements in the migratory routes of the relationship. Identical negative correlation coefficients in the system «soil-sediments» have Cu, Zn, Mn. There is a strong relationship for Cu, the average of Zn and Сd on average statistically significant, moderate on Pb and Co.